PENAHANAN PELAKU TINDAK PIDANA DI BAWAH UMUR OLEH PENYIDIK DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 3 TAHUN 1997 TENTANG PENGADILAN ANAK - Adi Sujarwo; Endeh Suhartini; Ju naidi (Fakultas Hukum Universitas Djuanda Bogor, 2016)
Delinquency problem is the actual problem, in almost all the countries in the world, including Indonesia . Attention to this issue has a lot of thought poured out, either in the form of discussions and seminars which have been held by organizations or government agencies that close relationship with this problem. In a legal perspective, the problem of theft is a criminal act (delict) plaguing the society , in Article 362 Code of Criminal Law of the theft said,